Distance Learning under the Covid-19 Conditions within Architectural Education - Emel Unver; Asli Sungur (Center for Educational Policy Studies Journal)
Distance learning is one of the means of education used in various levels, from primary school to college. However, distance learning in architectural education differs from other disciplines, as architectural education is design-based with predominantly applied courses. As the spring semester of the 2019/20 academic year had to continue online due to the Covid-19 pandemic and it remained uncertain whether or when face-to-face (FtF) education will start till the end of the term, the necessity to focus on online education suddenly raised in architectural faculties. This study aims to start a discussion on how to proceed with online architectural education, focusing on quality, defining the fundamentals, and proposing suggestions within this scope. In order to achieve this aim, research on the evaluation of the existing distance learning platforms of universities, the differences between the implementations of theoretical and applied courses, the advantages and disadvantages of the process are made. For this purpose, a comprehensive literature review on universities that provide fully online, hybrid and conventional (FtF) education throughout the world is conducted, given and discussed in the paper. After the research on ongoing processes, a case study to determine the experiences, opinions and approaches of students and academic staff with the scope of emergency remote teaching is designed and conducted. Together with the findings of the review and the case study, the challenges, strengths and opportunities of online architectural education are discussed and evaluated with a focus on maintaining and raising the quality of the education. In conclusion, suggestions and proposals are made and presented to be applied and developed in architecture faculties’ future online education experiences.